2011
DOI: 10.1590/s1809-48722011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Central Hearing Process in Parkinson Patients

Abstract: Summary Introduction: Parkinson disease (PD) is a degenerating disease with a deceitful character, impairing the central nervous system and causing biological, psychological and social changes. It shows motor signs and symptoms characterized by trembling, postural instability, rigidity and bradykinesia. Objective: To evaluate the central hearing function in PD patients. Method: A descriptive, prospect and transversal study, in which 10 individuals diagnosed of PD named study group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Multiple studies have addressed dichotic listening in a divided attention paradigm in patients with PD. Overall, these studies did not find significant group differences between patients with PD and HCs (20,22,67,68). Only Richardson et al (69) reported that a substantial part of patients with PD demonstrated abnormal dichotic listening compared to normative values.…”
Section: Dichotic Listening Testsmentioning
confidence: 86%
“…Multiple studies have addressed dichotic listening in a divided attention paradigm in patients with PD. Overall, these studies did not find significant group differences between patients with PD and HCs (20,22,67,68). Only Richardson et al (69) reported that a substantial part of patients with PD demonstrated abnormal dichotic listening compared to normative values.…”
Section: Dichotic Listening Testsmentioning
confidence: 86%